National Athletic Trainers' Association Position Statement: Fluid Replacement for the Physically Active - McDermott, Brendon P. (J Athl Train, 2017)
OBJECTIVE: : To present evidence-based recommendations that promote optimized fluid-maintenance practices for physically active individuals. BACKGROUND: : Both a lack of adequate fluid replacement (hypohydration) and excessive intake (hyperhydration) can compromise athletic performance and increase health risks. Athletes need access to water to prevent hypohydration during physical activity but must be aware of the risks of overdrinking and hyponatremia. Drinking behavior can be modified by education, accessibility, experience, and palatability. This statement updates practical recommendations regarding fluid-replacement strategies for physically active individuals. RECOMMENDATIONS: : Educate physically active people regarding the benefits of fluid replacement to promote performance and safety and the potential risks of both hypohydration and hyperhydration on health and physical performance. Quantify sweat rates for physically active individuals during exercise in various environments. Work with individuals to develop fluid-replacement practices that promote sufficient but not excessive hydration before, during, and after physical activity.